Isolation and Preliminary Characterization of Fusarium sp. from Diseased Cardamom and Screening of Bacterial Antagonists - Rai, Ganga Bir; Thapa, Niru; Dhal, Shiv; Kayastha, Saru; Paudel, Anu; Wasti, Anupama; Khadka, Deegendra; Malla, Sailesh; Subba, Bimala (Journal of Nepal Biotechnology Association, 2026)
Fusarium species are frequently associated with plant diseases affecting economically important crops, including cardamom (Amomum subulatum Roxb.). In this study, a fungal isolate was recovered from diseased cardamom stems collected in Panchthar district, Nepal, and characterized using morphological observations and ITS rDNA sequencing. The isolate was identified as Fusarium sp. isolate CS2 showing similarity to members of Fusarium species. A wheat seed assay demonstrated fungal colonization, but no visible disease symptoms were observed on wheat seedlings under the tested conditions, likely reflecting that wheat is not the natural host of the isolate. Three bacterial isolates were screened for antagonistic activity against the fungal isolate using dual culture assays. Among them, isolate BGNC-B10, tentatively identified as a putative Exiguobacterium-like bacterium based on partial 16S rRNA gene sequencing, showed moderate inhibition of fungal growth, reaching 35.97 ± 2.6% inhibition at Day 6. Inhibition declined to approximately 15% at later incubation times, and the treatment effect was not statistically significant (p = 0.092). The isolate also produced extracellular protease on skim milk agar. These findings indicate BGNC-B10 exhibits moderate in vitro antagonistic activity against Fusarium isolate associated with diseased cardamom. However, pathogenicity toward cardamom was not confirmed.